INNV-40. TARGETED NEXT GENERATION SEQUENCING OF PEDIATRIC HIGH-GRADE GLIOMA AND ITS THERAPEUTIC IMPLICATIONS, MD ANDERSON EXPERIENCE. (11th November 2019) - McCall, David; Eterovic, Agda; Moss, Tyler; Baig, Muhammed; Fuller, Greg; Huse, Jason; Sandberg, David I; Rytting, Michael; Gill, Jonathan; Chandra, Joya; Khatua, Soumen; Shaw, Kenna; et al.
Abstract: INTRODUCTION: The new understanding of molecular pathways in cancer is paving the way towards personalized cancer medicine, especially in refractory disease. High-grade gliomas (HGG) are common pediatric brain tumors that tend to recur, with no available standard therapy upon recurrence. HGG are challenging tumors with illusive biology and poor outcome. We report here the molecular testing of 27 pediatric HGG patients. MATERIALS AND METHODS: An analysis of pediatric patients with HGG treated at UT MD Anderson Cancer Center (MDACC) who underwent molecular genetic profiling using next generation sequencing with different genomic panels (AmpliSeq™Cancer Hotspot and Oncomine Panels – by Thermo Fisher Scientific). RESULTS: 27 patients with HGG (median age 14 years, range 3–18 years old) underwent genomic profiling. Primary diagnoses were glioblastoma multiforme (n=22), anaplastic astrocytoma (n = 2), gliosarcoma (n= 1), anaplastic pleomorphic xanthoastrocytoma (n= 1) and anaplastic oligoastrocytoma (n= 1). There are 46 genes common to the panels used. The most common mutation was in TP53 (73%). Other mutations included PIK3CA (19%), IDH1 (11.5%), 7.7% for ATM, EGFR and PTEN, and 3.8% for BRAF, FGFR1 and FGFR2. 24 out of 27 patients were tested at initial diagnosis and 3 upon relapse/progression. Patients at initial diagnosis received standard of care therapy of radiation and temozolomide. Only 5 patients received targeted therapy upon progression/recurrence. Some challenges of genomically-matched therapy included lack of clinical trials accepting pediatric patients, unavailability of a liquid form of a drug, and insurance disapproval for off-label use. CONCLUSION: The next generation of therapy for childhood cancers will be based upon in-depth molecular phenotyping that may facilitate the development of rational risk-adapted and target-based therapies. This cohort, though limited by sample size, highlights the opportunity to perform molecular testing and identification of alterations in actionable genes.